Prawo pacjenta do opieki duszpasterskiej - Aleksandra Klich (Studia Paradyskie)
The publication focuses on the right of patients to pastoral care during hospitalization. Based on current legislation, patients have the right to receive pastoral care in accordance with their religious or spiritual beliefs. In the context of health care, these rights include access to chaplains or clergy, the ability to practice religious observances, and the provision of emotional support in accordance with one's beliefs. It is crucial to guarantee patients' autonomy in choosing pastoral care, regardless of their religion. The purpose is to highlight the need to professionalize pastoral care services, as well as the organizational problems associated with imposing an obligation on the treatment entity to ensure the realization of the patient's right to pastoral care.